The Effect of Regional Original Income and general allocation funds on Regional Expenditures on South Bolaang Mongondow Regency - Ohy, Marzanzius Arvan; Bogar, Wilson; Mandagi, Marthinus (Technium Social Sciences Journal, 2021)
The purpose of this study was to determine how much influence revenue (PAD) and general allocation fund (DAU) to spending in South Bolaang Mongondow area, either partially or simultaneously. This research is quantitative by using secondary data from the Budget Realization Report Revenue and Expenditure in local government South Bolaang Mongondow. This study indicates that Regional Original Income and general allocation funds positive and significant effect on Regional Expenditures. With the results of the first t-test analysis of 0.003 <0.05 and the t-count value of 3.975 > t-table 2.262, the second t-test of 0.003 <0.05 and the t-count value of 4.103> t table 2,262, and there is a simultaneous influence of Regional Original Revenue and general allocation funds on Regional Expenditures with F test analysis of 0.008 < 0.05 and F arithmetic value 8.823 > F table 4.10. Thus, regional Original Revenue and general allocation funds simultaneously or together positively influenced Regional Expenditures for South Bolaang Mongondow Regency in 2009-2020, expected that government areas to continue to improve reception on local revenue sources to create local independence. Besides the local government, South Bolaang Mongondow must also manage allocation funds with the right target.